Behavioral Counseling Guidebook with Discussion Techniques and Positive Reinforcement to Increase High School Students' Self-confidence - Ni Nyoman Janaki Priya Dewi Dasi; Putu Ari Dharmayanti; Dewi Arum W.M.P. (Bisma The Journal of Counseling, 2023)
The large number of students who are still shy about expressing opinions and easily feel nervous when doing something shows that the level of self-confidence of students is still relatively low. To overcome these problems, we need media guidance that can help increase student self-confidence. This research aims to produce a product as a behavioral counseling guidebook with discussion techniques and positive reinforcement to increase student self-confidence. This research belongs to the development research developed using the 4D model through the stages of defining, designing, developing, and disseminating. The subjects involved in this study were five experts/practitioners in guidance and counseling and 32 high school students. Data collection in the study was carried out using questionnaires online via Google form, with the research instrument as a media validity test sheet. The data obtained in the study were then analyzed using the CVR (Content Validity Ratio), CVI from Lawshe, and the t-test. The results of the research analysis show that the probability value is 0.000. When compared with a significance level of 0.005, this certainly shows that the significance level is greater than the probability of the data. Based on these results, it can be concluded that a behavioral counseling guidebook with discussion techniques and positive reinforcement to increase high school students' self-confidence is feasible to implement and use in the guidance process.